Developement of Prediction in Clients' Consent to a Bank Term Deposit Using Feature Selection - Morani, Kinan; Ayana, Esra Kaya; Engin, Seref Naci (IEEE, 2018)
This paper presents the effect of Feature Selection on the accuracy of predictive results. It shows that using feature selection algorithms help to get almost the same accurate results comparing to when feature selection is not used. However, the results show that implementing feature selection algorithms reduces data processing time and gives more flexibility in the software package selection since smaller amount of data is resulted.
Keywords: Artificial Neural Networks; Feature Selection; Cross Validation; Sequentail Forward Selection; Mean Square Erorr; Regression; Automation & Control Systems; Computer Science; Engineering